La Historia general de España de Juan de Mariana y su relación con la Edad Media - Ferrás García, Iago Brais (Historiografías, 2021)
This article studies the Historia general de España by Juan de Mariana understood as a part of historiographic transition taken place between the Middle Ages and the Modern Age, its purpose being to identify a double absence: the absence of awareness on the part of Juan de Mariana that he is narrating a Middle Ages, and the lack of reflections on the idea of Middle Ages throughout the work. We shall begin with a contextual analysis of the Historia general de España to understand it within the reality in which it was written. Then, we shall attend the reception of both the work and its author. Finally, we reflect on the idea of medieval history in the Historia general de España, how the concept of the Middle Ages was born and how the Middle Ages is being written in this time, specifically in the text by Mariana. Key Words Juan de Mariana, Historia general de España, medieval historiography, medieval history, Middle Ages